STUDI AGROINDUSTRI AMPLANG TENGGIRI DI KOTA PEKANBARU - Eliza '; Jumar ' (Jurnal Sagu, 2003)
The purpose of this study wa to analize some aspects of the business such as technical and technological,marketing, management, juridiscal, financial and environmental aspectsusing case .study. This researchstarted from August to December 2001. The results show that this industry still used simple technology andequipment The ingredients of the product are tenggiri fish, tapioca, sugar, salt, egg, fried oil and vetsin. Therearc two ways ofdistributioas, the first is by distributing the product directly to the consumers and the secondis through retail traders. The marketing of this product has reached many places such as Malaysia andSingapura. The system of work used was a cooperation system and there was no such kind of the companystructure. The industry of Amplang Tenggiri Sumber Rezeki has been stated legally based upon the instruc-tion from the Departcment of Public Health Rl No. SP. 004/04.01/1992/14. The RCR value attained was 2,95.Il nieaas that every one rupiah of cost production will earn 2,95 nipiahs of gross profit or the profit is about Rp1,95. The gross profit earned by the enterpreneur in a month was Rp 43.940.000,- and the net income was Rp29.084.044,4.3. From the observation and analysis of the business, agroindustry of amplang tenggiri SumberRexeki is feasible to be developed in the future. In the view point of environment, thi-s Industry did not cause anydisti-ubances to the people and surroundings, based on the statement of the people living around this homeindustry.